Reduced match exposure in the previous 2 matches accounts for hamstring muscle injury incidence in professional football players - Moreno-Pérez, V.; Del Coso, J.; López-Del Campo, R.; Resta, R.; Romero-Sangüesa, J.; Courel-Ibáñez, J.; Méndez-Villanueva, A. (Sports Health: A Multidisciplinary Approach, 2024)
Background: Hamstring strain injuries are one of the most prevalent injuries in football (soccer). We examined the influence of accumulated match-play exposure on the occurrence of hamstring strain injury in professional football from 2 teams (Spanish 1st Division, LaLiga) over 3 seasons, and determined specific cut-off points as indicators of injury risk.